Characterization of hydrogel structural damping. (October 2020) - Wang, Bohan; Moura, Adriane G.; Chen, Jiehao; Erturk, Alper; Hu, Yuhang
Abstract: Gels are composed of crosslinked polymer networks and solvent molecules imbibed into the networks. Gels are both ubiquitous in nature and important engineering materials widely used in many applications. Due to their biocompatibility, stimuli-responsiveness, and compliance, gels gain an edge over traditional materials, such as metals and composites in many modern engineering applications. In the past, the static and kinetic properties of gels have been widely studied. However, the dynamic properties of gels, particularly their structural damping, remain largely unknown even though gels are often under dynamic conditions in various applications. The literature of soft materials is lacking both damping data for hydrogels and a standard testing method to that end. This work reports experimentally identified structural damping data for a set of hydrogel samples via resonant vibration tests for the first bending mode. Beam-shaped samples of rectangular cross-section are clamped vertically at both ends and tested under linear base excitation. An analysis of the frequency response functions based on the Euler–Bernoulli beam theory is conducted to extract Young's modulus and structural damping values. In the experiments, polyacrylamide gels of three different compositions and polydimethylsiloxane (PDMS) elastomers of two different compositions are prepared and tested. The remarkable result is that the hydrogels have 80% less damping than PDMS, even though hydrogels are an order of magnitude softer than PDMS. The molecular origins of the damping in hydrogels and PDMS are discussed. The low damping of gels may open new avenues of research and applications of soft materials in structural dynamics and wave propagation, such as metamaterials and topological insulators, among others.